High performance scientific computing using FPGAS with IEEE floating point and logarithmic arithmetic for lattice QCD - PEARDON, MICHAEL JAMES (IEEE, 2006)
The recent development of large FPGAs along with the availability of a variety of floating point cores have made it possible to implement high-performance matrix and vector kernel operations on FPGAs. In this paper we seek to evaluate the performance of FPGAs for real scientific computations by implementing Lattice QCD, one of the classic scientific computing problems. Lattice QCD is the focus of considerable research work worldwide, including two custom ASIC-based solutions. Our results give significant insights into the usefulness of FPGAs for scientific computing. We also seek to evaluate two different number systems available for running scientific computations on FPGAs. To do this we implement FPGA based lattice QCD processors using both double precision IEEE floating point and single precision equivalent Logarithmic Number System (LNS) cores and compare their performance with that of two lattice QCD targeted ASIC based solutions and with PC cluster based solutions.
PUBLISHED
Keywords: Pure & Applied Mathematics